Young people and noncommunicable diseases – vulnerable to disease, vital for change - Marie Hauerslev (International Journal of Noncommunicable Diseases, 2018)
Youth have a right to health, but that is not adequately reflected in our societies and health systems. In fact, for cancer, diabetes, chronic lung disease, and cardiovascular diseases - so-called noncommunicable diseases (NCDs) - more than two-thirds of preventable adult deaths are associated with behavior that started in adolescence. Many young people are well aware of how drastically NCDs will affect their generation in the current system and have taken the challenge to change the discourse for a healthier global population. Yet, youth voices are often dismissed or tokenized in political conversations. This is despite the many examples of youth making positive change at all levels of society. This paper provides an overview of the challenges and emerging youth-driven actions to address NCDs at local, national, and global levels.